Bioprospecting Amazonian yeasts for ethanol and xylitol production from sugarcane bagasse hydrolysate - Leissandra Nascimento Castelo; Filipe Soares de Freitas; Raphael Ferreira Rocha; Edson Junior do Carmo; Enedina Nogueira de Assunção; Sônia Maria da Silva Carvalho; Lílian de Araújo Pantoja; Ítalo Thiago Silveira Rocha Matos; Spartaco Astolfi Filho; Alexandre Soares dos Santos (Systems Microbiology and Biomanufacturing, 2026)
The untapped microbial diversity of the Amazon region represents a strategic frontier for biotechnological applications. This study screened, identified, and evaluated the potential of yeasts isolated from Amazonian environments to bioconvert sugarcane bagasse hydrolysate into ethanol and xylitol. The lignocellulosic hydrolysate was obtained by thermochemical treatment using H 2 SO 4 (0.78% v/v) at 121 °C for 68 min, with a 20% solid loading. The yeast-like isolates were identified by sequencing the internal transcribed spacer (ITS) region (5.8S rDNA) and the D1/D2 domain of the 26S rDNA. Fifteen strains belonging to the genera Pichia , Debaryomyces , Meyerozyma , and Cyberlindnera exhibited the native capacity to convert xylose into xylitol and/or ethanol, achieving product yields ( Y P/S ) of up to 0.20 g g − 1 for ethanol and 0.25 g g − 1 for xylitol in synthetic medium. Although initial fermentation in the acid hydrolysate (28.9 g L − 1 xylose, 5.0 g L − 1 arabinose, 1.2 g L − 1 glucose, and 5.9 g L − 1 acetic acid) supported cell growth, product synthesis was strongly inhibited by the high concentration of byproducts. The use of a biomass deacetylation strategy reduced acetic acid levels to 1.0 g L − 1 , enabling the conversion of sugars into the desired alcohols. Cyberlindnera saturnus strains achieved Y P/S of up to 0.10 g g − 1 for ethanol and 0.14 g g − 1 for xylitol on deacetylated hydrolysate, while simultaneously performing the bioabatement of furans and residual acetic acid. These findings highlight unconventional Amazonian yeasts that, pending bioprocess optimization, exhibit promising metabolic traits for lignocellulosic biorefineries, including potential new yeast taxa.

Carvacrol incorporated on raw and acid-activated vermiculites and their antibacterial evaluation - José de Souza; Lucilane Gomes Oliveira; Luís Humberto Oliveira; Josy Anteveli Osajima; Edson Cavalcanti Silva-Filho; Santiago Medina-Carrasco; Maria del Mar Orta Cuevas; Maria Gardênnia Fonseca (Applied Clay Science, 2026)

Commercial graphene oxides show distinct suitability for silver-nanocomposite formation and antibiofilm activity and cytocompatibility - Thamyres Freire da Silva; Francisco Fábio Pereira de Souza; Thiago Alves de Moura; Luciano Ferreira de Almeida; Maria Rosiene Antunes Arcanjo; Antônio Gomes de Souza Filho; Adriano Lincoln Albuquerque Mattos; Juan Antonio Cecilia; Enrique Rodriguez-Castellon; Henry Kobs; Andreia Fonseca de Faria; Maria Kelva do Carmo; et al. (In vitro models, 2026)

Influence of agricultural residues on the formation of TiO2 phases: Real-time in situ X-ray diffraction monitoring in a reaction chamber - Rodrigo P. Feitosa; Johar Amin Ahmed Abdullah; Ramón R. Peña-Garcia; Maria G. Fonseca; Edson C. Silva-Filho; Santiago Medina-Carrasco; Maria del Mar Orta Cuevas; Josy A. Osajima (Chemical Engineering Journal, 2026)

Chemical composition and acaricidal activity of essential oils from Alpinia zerumbet, Bixa orellana, Mesosphaerum suaveolens and Syzygium cumini against Oligonychus punicae on clonal seedlings of Eucalyptus grandis - Adriele de Castro Ferreira; Rosenya Michely Cintra Filgueiras; Paulo Roberto Ramalho Silva; Izaias Santos Marques; Antonio José Cantanhede Filho; Bruno de Araújo Gomes; Edson Rodrigues Filho; Franciele Costa de Sousa; Eslane Reis Farias Mendes; Helane Cristina De Andrade Rodrigues Severo; Alyne Freire de Melo; Kamilla de Andrade Dutra; et al. (Crop Protection, 2026)

The incorporation of thymol and carvacrol in bentonites: Influence of functionalization and the resulting antibacterial activities - Luís H. Oliveira; Idglan S. de Lima; Denise B. França; Albert S. Silva; Santiago Medina-Carrasco; Maria del Mar Orta; Josy A. Osajima; Maria G. Fonseca; Edson C. da Silva-Filho (Applied Clay Science, 2026)

Encapsulation of slow-release urea in stearic acid microspheres: Effects on nutrient digestibility, nitrogen utilization, and performance in lambs - Everton C. de. Medeiros; André L. da Silva; José Morais Perreira Filho; Kevily H. de O.S. de Lucena; Gildênia A. Pereira; Mônica T. Cavalcanti; Juliana P.F. de Oliveira; Elzania S. Pereira; Edson C. Silva Filho; Leilson R. Bezerra (Animal Feed Science and Technology, 2026)

The Impact of Growth-Promoting Bacteria and Residual Phosphorus Rates on the Nutritional Efficiency and Production of Ratoon Sugarcane - Guilherme Carlos Fernandes; Poliana Aparecida Leonel Rosa; Fernando Shintate Galindo; Carlos Eduardo da Silva Oliveira; Shereen Magdy Korany; Hana Sonbol; Emad Ali Alsherif; Seham M. Hamed; William Cesar Nishimoto Ito; Gabrielly Freire Torrezan; Renato Lustosa Sobrinho; Caio Henrique Oliveira Schussler; et al. (Sugar Tech, 2025)

Innovative properties of sustainable galactomannans from seeds of Adenanthera pavonina, Caesalpinia pulcherrima and Delonix regia - Marcilia P. Costa; Maurycyo S. Geronço; Igor F. da S. Ramos; Monalisa de A. Lucena; Ricardo Araújo; Iluska M. Pinheiro; Rayran Walter R. de Sousa; Paulo Michel P. Ferreira; Josy A. Osajima; Manuela Amorin; Óscar Ramos; Edson C. Silva-Filho; et al. (Carbohydrate Polymers, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

Ancient materials for new applications: The combination of montmorillonite with polysaccharides for biomedical uses - Lucilane Gomes Oliveira; Denise Brito França; Josy Anteveli Osajima; Edson Cavalcanti Silva-Filho; Santiago Medina-Carrasco; Maria Del Mar Orta; Maguy Jaber; Maria Gardênnia Fonseca (Applied Clay Science, 2025)

Cashew gum as future multipurpose biomacromolecules - Tarcísio Mendes Silva; Antônia Carla De Jesus Oliveira; Amanda Damasceno Leão; Renata Kelly Luna Gomes Ramos; Luise Lopes Chaves; Edson Cavalcanti da Silva-Filho; Monica Felts de La Roca Soares; José Lamartine Soares-Sobrinho (Carbohydrate Polymers, 2025)

Cytotoxicity and genotoxic impacts of LAPONITE® on murine adipose stem cells - Francisca L.A. Cardoso; Letícya L.S. Soares; Danielle B.A. Silva; Napoleão M. Argôlo Neto; Edson C. Silva Filho; Adalberto S. Silva; Dayseanny O. Bezerra; Maria S.P. Cruz; Felipe C. Nunes; Wanderson G.G. Melo; João M.C. Sousa; Antonielly C. Reis; et al. (Applied Clay Science, 2024)

A new method for reducing impurities in clay minerals - Joaldo S. Lopes; Marcelo L. Morais; Alan I.S. Morais; Roosevelt D.S. Bezerra; Josy A.O. Furtini; Edson C. Silva Filho (Applied Clay Science, 2024)

ZnO-Saponite Nanocomposite: Input of Adsorption and Photocatalysis for Removal of Rhodamine B Dye - Dihêgo H. Damaceno; Pollyana Trigueiro; Luciano Clécio Brandão Lima; Luzia M. Honorio; Ramón Peña-Garcia; Marcelo B. Furtini; Yuset Guerra; Maria Gardennia Fonseca; Edson C. da Silva-Filho; Maguy Jaber; Josy A. Osajima (Water, Air, & Soil Pollution, 2024)

Organo magadiites for diclofenac adsorption: influence of the surfactant chain - Denise de Brito França; Daniele Pereira da Costa; Edson Cavalcanti da Silva-Filho; Josy Anteveli Osajima; Santiago Medina-Carrasco; Maria Del Mar Orta Cuevas; Maguy Jaber; Maria Gardennia Fonseca (Environmental Science and Pollution Research, 2024)

Bacteria isolated from Aedes aegypti with potential vector control applications - Juan Campos de Oliveira; Ricardo de Melo Katak; Veranilce Alves Muniz; Marta Rodrigues de Oliveira; Elerson Matos Rocha; William Ribeiro da Silva; Edson Júnior do Carmo; Rosemary Aparecida Roque; Osvaldo Marinotti; Olle Terenius; Spartaco Astolfi-Filho (Journal of Invertebrate Pathology, 2024)

Preparation and release of antibacterial Na-mica-4/chlorhexidine nanocomposites - Luís H. Oliveira; Idglan S. de Lima; Denise B. França; Alan I.S. Moraes; Maria G. Fonseca; Humberto M. Barreto; Santiago Medina-Carrasco; Josy A. Osajima; Edson C. da Silva-Filho; María del Mar Orta (Applied Clay Science, 2024)

Evaluation of internal markers in digestibility estimation for sheep and goats - Michel Alves da Silva; Juliana Silva de Oliveira; Edson Mauro Santos; Gabriel Ferreira de Lima Cruz; Gherman Garcia Leal de Araújo; Márcia Maria Cândido da Silva; Gilberto de Carvalho Sobral; João Paulo de Farias Ramos; Paloma Gabriela Batista Gomes; Guilherme Medeiros Leite; Maria Alyne Coutinho Santos; Paulo da Cunha Torres Júnior; et al. (Tropical Animal Health and Production, 2024)

Polyurethane sponges bearing cucurbituril adsorb Cr(III) and Pb(II) ions from contaminated water samples - Lilian Rodrigues Rosa Souza; Renato Salviato Cicolani; Bruno Edson Santana de Freitas; Giovana Lavezo Floriano; Maycon Lucas de Oliveira; Antonio Gustavo Sampaio de Oliveira Filho; Márcia Andreia Mesquita Silva da Veiga; Gregoire Jean-François Demets (Environmental Science and Pollution Research, 2024)

Does non-steroidal anti-inflammatory drugs-related preemptive analgesia modulate SOCS3/IL-6 pathway in oral surgery? - Assis Filipe Medeiros Albuquerque; José Jackson do Nascimento Costa; José Roberto Viana Silva; Paulo Goberlânio de Barros Silva; Filipe Nobre Chaves; Eduardo Frederico Eduardo Maferano; Edson Luiz Cetira Filho; Karuza Maria Alves Pereira; Sérgio Lima Santiago; Thyciana Rodrigues Ribeiro; Fábio Wildson Gurgel Costa (Inflammopharmacology, 2024)

An overview about synthetic high charge micas and their uses - Luís H. Oliveira; Denise B. França; Alan I.S. Moraes; Santiago Medina-Carrasco; Maria G. Fonseca; Josy A. Osajima; Edson C. da Silva-Filho; María del Mar Orta (Applied Clay Science, 2024)

Slow-releasing urea coated with low-trans vegetable lipids: Effects on lamb performance, nutrient digestibility, nitrogen balance, and blood parameters - Kevily H. de O.S. de Lucena; Pedro H.S. Mazza; Ronaldo L. Oliveira; Analivia M. Barbosa; José M. Perreira Filho; Rui J.B. Bessa; Susana P. Alves; Ricardo L. Edvan; Elzania S. Pereira; Mozart Fonseca; Edson C. Silva Filho; Leilson R. Bezerra (Animal Feed Science and Technology, 2024)

Effect of slow-release urea on intake, ingestive behavior, digestibility, nitrogen metabolism, microbial protein production, blood and ruminal parameters of sheep - Aline Silva; José Morais Pereira Filho; Juliana Oliveira; Kevily Lucena; Pedro Mazza; Edson Silva Filho; Ariane Nascimento; Elzânia Pereira; Antônio Vaz; Analivia Barbosa; Ronaldo Oliveira; Leilson Bezerra (Tropical Animal Health and Production, 2023)

Essential oil in bentonite: Effect of organofunctionalization on antibacterial activities - Luís H. Oliveira; Idglan S. de Lima; Enedina R. da S. Neta; Sidney G. de Lima; Pollyana Trigueiro; Josy A. Osajima; Edson C. da Silva-Filho; Maguy Jaber; Maria G. Fonseca (Applied Clay Science, 2023)

Is coadministration of preemptive medications an effective strategy for reducing inflammatory clinical events and the need for rescue medication after mandibular third molar surgery? A systematic review of randomized clinical trials - Edson Luiz Cetira-Filho; Paulo Ricardo Martins-Filho; Paulo Goberlânio de Barros Silva; Pedro Henrique da Hora Sales; Alessandra Fragoso Vieira; Lívia Maria Eugênio Sindeaux; Mayara Oliveira dos Anjos; Jair Carneiro Leão; Fábio Wildson Gurgel Costa (Inflammopharmacology, 2023)

Adsorption of tetracycline using chitosan–alginate–bentonite composites - Francisco G. Nunes Filho; Edson C. Silva Filho; Josy A. Osajima; Ana Paula de Melo Alves; Maria Gardênnia Fonseca (Applied Clay Science, 2023)

Synthetic dibenzylideneketones as promising anti-herpes simplex virus type 1 agents - Thalita Zago Oliveira; Dyenefer Pereira Fonseca; André Henrique dos Santos; Thays Rosa da Silva; Danielle Lazarin-Bidóia; Zia Ud Din; Benedito Prado Dias Filho; Celso Vataru Nakamura; Edson Rodrigues-Filho; Tania Ueda-Nakamura (Archives of Virology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Saponite-inspired Materials as Remediation Technologies for Water Treatment: an Overview - Dihêgo Henrique L. Damacena; Pollyana Trigueiro; Victor Hugo Monteiro; Luzia Maria C. Honorio; Thiago Marinho Duarte; Robson Cunha; Marcelo B. Furtini; Maria Gardennia Fonseca; Edson C da Silva-Filho; Josy A. Osajima (Environmental Processes, 2023)

Effects of Euterpe oleracea Mart. extract on Candida spp. biofilms - Larissa Lira Brito; Kátia Regina Assunção Borges; Gabriel Xavier Silva; Marcos Antonio Custódio Neto da Silva; Rita de Nazaré Silva Alves; Amanda Mara Teles; Maria do Carmo Lacerda Barbosa; Walbert Edson Muniz Filho; Geusa Felipa de Barros Bezerra; Maria do Desterro Soares Brandão Nascimen (Brazilian Journal of Microbiology, 2023)

Improved remediation of contaminated water using ZnO systems via chemical treatment: applications, implications and toxicological mitigation - Josy A. Osajima; Alexandro S. Sá; Rodrigo P. Feitosa; Marcelo B. Furtini; Luzia M. C. Honorio; Maria G. Fonseca; Pollyana Trigueiro; Paula Caregnato; Eduardo R. Triboni; Edson C. Silva-Filho (Sustainable Water Resources Management, 2023)

Evaluation of the in vivo safety of tucumã oil nanocapsules in an experimental model of silver catfish Rhamdia quelen - Kátia Nascimento; Matheus Dellaméa Baldissera; Carine de Freitas Souza; Gerson Fernandes de Brum; Andiara Prates Ramos; Roberta Cougo Riéffel; Lauren Pappis; Walter Paixão de Sousa Filho; André Gundel; Alencar Kolinski Machado; Aline Ferreira Ourique; Bernardo Baldisserotto; et al. (Natural Product Research, 2022)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Au@Ag bimetallic nanoparticles deposited on palygorskite in the presence of TiO2 for enhanced photodegradation activity through synergistic effect - Josy A. Osajima; Alexandro S. Sá; Luzia M. C. Honorio; Pollyana Trigueiro; Lucas I. F. Pinto; Joziel A. Oliveira; Marcelo B. Furtini; Roosevelt D. S. Bezerra; Ana C. S. Alcantara; Edson C. Silva-Filho (Environmental Science and Pollution Research, 2021)

Nitrogen use efficiency and recovery in a wheat-corn rotation under tropical savannah conditions - Fernando Shintate Galindo; Edson Cabral da Silva; Paulo Humberto Pagliari; Guilherme Carlos Fernandes; Willian Lima Rodrigues; Antônio Leonardo Campos Biagini; Eduardo Bianchi Baratella; Castro Alves da Silva Júnior; Mário João Moretti Neto; Takashi Muraoka; Marcelo Carvalho Minhoto Teixeira Filho (Nutrient Cycling in Agroecosystems, 2021)

Rainfall extremes and drought in Northeast Brazil and its relationship with El Niño–Southern Oscillation - Micejane da Silva Costa; José Francisco de Oliveira‐Júnior; Paulo José dos Santos; Washington Luiz Félix Correia Filho; Givanildo de Gois; Cláudio José Cavalcante Blanco; Paulo Eduardo Teodoro; Carlos Antonio da Silva Junior; Dimas de Barros Santiago; Edson de Oliveira Souza; Alexandre Maniçoba da Rosa Ferraz Jardim (International Journal of Climatology, 2021)
The objective of this study was to evaluate the annual standardized precipitation index (SPI) obtained from the DrinC software based on multivariate analysis in the identification of rainfall and drought extremes in the State of Alagoas and its relationship with El Niño–Southern Oscillation. Monthly rainfall data from 1960 to 2016 from National Water Agency were analysed. Annual SPI (SPI‐12) has been designed for comparison with ENSO phases via Oceanic Niño Index for 3.4 region and in identifying climate extremes in the State of Alagoas. The principal component analysis and cluster analysis techniques were applied to the rainfall series of SPI‐12. Extreme events were identified in both rainy and drought periods according to SPI‐12, and were associated with the ENSO phases (El Niño, La Niña, and Neutral). The first four principal components explained 46.68% of the variance. Our findings are crucial for agriculture and civil defence since northeastern Brazil has several areas of risk and social vulnerability.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Industrial Quality of Sugarcane Under Fertigation with Nitrogen and Zinc - Fernando Nobre Cunha; Marconi Batista Teixeira; Frederico Antonio Loureiro Soares; Edson Cabral da Silva; Antonio Evami Cavalcante Sousa; Leonardo Nazário Silva dos Santos; Nelmício Furtado da Silva; Wilker Alves Morais; Vitor Marques Vidal; Fernando Rodrigues Cabral Filho; Gustavo da Silva Vieira (Sugar Tech, 2020)

Reaction to drought stress of citrus progenies with potential use for rootstocks development - Lizziane Gomes Leal Santana; Edson dos Santos Souza; Carlos Alberto da Silva Ledo; Orlando Sampaio Passos; Mauricio Antônio Coelho Filho; Abelmon da Silva Gesteira; Walter dos Santos Soares Filho (Brazilian Journal of Botany, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The occurrence of wild cotton Gossypium mustelinum Miers ex Watt populations in the coast of Pernambuco, Northeastern Brazil - Edson Ferreira da Silva; Luiz Sergio Costa Duarte Filho; Ana Kelly dos Santos Maia; Allison Vieira da Silva; Ana Carolina Borges Lins e Silva (Genetic Resources and Crop Evolution, 2018)

Effective Removal of the Remazol Yellow GR Dye Using Cellulose Functionalized by Basic Groups - Lucinaldo S. Silva; Mateus S. Silva; Francisco J. L. Ferreira; Luciano C. B. Lima; Roosevelt D. S. Bezerra; Antônia M. G. L. Citó; Josy A. Osajima; Edson C. Silva Filho (Water, Air, & Soil Pollution, 2018)

Differentially expressed proteins associated with drought tolerance in bananas (Musa spp.) - Lorenna Alves Mattos-Moreira; Claudia Fortes Ferreira; Edson Perito Amorim; Carlos Priminho Pirovani; Edson Mario de Andrade; Mauricio Antônio Coelho Filho; Carlos Alberto da Silva Ledo (Acta Physiologiae Plantarum, 2018)

Remediation of Phenanthrene-Contaminated Soil by Persulfate Activated with Fe-Modified Diatomite: Kinetic and Statistical Approaches - Celyna K. O. Silva-Rackov; Leandro G. Aguiar; Alessandra R. Souza; Silvia S. O. Silva; Alan G. Câmara; Marilda M. G. R. Vianna; Edson L. Foletto; Claudio A. O. Nascimento; Osvaldo Chiavone-Filho (Water, Air, & Soil Pollution, 2017)

A3K2A3-induced apoptotic cell death of Leishmania amazonensis occurs through caspase- and ATP-dependent mitochondrial dysfunction - Francielle Pelegrin Garcia; Jean Henrique da Silva Rodrigues; Zia Ud Din; Edson Rodrigues-Filho; Tânia Ueda-Nakamura; Rachel Auzély-Velty; Celso Vataru Nakamura (Apoptosis, 2017)

Optimizing Phenanthrene and Anthracene Oxidation by Sodium Persulfate and Fe-Modified Diatomite Using the Response Surface Method - Celyna K. O. da Silva; Marilda M. G. R. Vianna; Edson L. Foletto; Osvaldo Chiavone-Filho; Claudio A. O. do Nascimento (Water, Air, & Soil Pollution, 2015)

Effect of Inorganic Salt Mixtures on Phenol Mineralization by Photo-Fenton-Analysis via an Experimental Design - Syllos Santos da Silva; Osvaldo Chiavone-Filho; Eduardo L. de Barros Neto; Edson Luiz Foletto; André Luís N. Mota (Water, Air, & Soil Pollution, 2014)

Assessing the use of erosion modeling to support payment for environmental services programs - Jorge Enoch Furquim Werneck Lima; Walszon Terllizzie Araújo Lopes; Fabiana de Gois Aquino; Eduardo Cyrino Oliveira-Filho; Edson Eyji Sano; Felippe Damião Mello di Silva (Journal of Soils and Sediments, 2013)

Mauritic acid: a new dammarane triterpene from the roots of Mauritia flexuosa L.f. (Arecaceae) - Hector H.F. Koolen; Elzalina R. Soares; Felipe M.A. da Silva; Aimêe A. de Oliveira; Antonia Q.L. de Souza; Lívia S. de Medeiros; Edson Rodrigues-Filho; Bruno C. Cavalcanti; Cláudia O. Pessoa; Manoel O. Moraes; Marcos J. Salvador; Afonso D.L. de Souza (Natural Product Research, 2013)

Brazilian Palygorskite as Adsorbent for Metal Ions from Aqueous Solution—Kinetic and Equilibrium Studies - Andrea M. B. M. Oliveira; Luiz F. O. Coelho; Saloana S. S. Gomes; Israel F. Costa; Maria G. Fonseca; Kaline S. de Sousa; José G. P. Espínola; Edson C. da Silva Filho (Water, Air, & Soil Pollution, 2013)

An antimicrobial diketopiperazine alkaloid and co-metabolites from an endophytic strain of Gliocladium isolated from Strychnos cf. toxifera - Hector Henrique Ferreira Koolen; Elzalina Ribeiro Soares; Felipe Moura Araújo da Silva; Antonia Queiroz Lima de Souza; Lívia Soman de Medeiros; Edson Rodrigues Filho; Richardson Alves de Almeida; Ismael Alexandre Ribeiro; Cláudia do Ó Pessoa; Manoel Odorico de Morais; Patrícia Marçal da Costa; Afonso Duarte Leão de Souza (Natural Product Research, 2012)

Electrophysiological Responses of Female and Male Hypsipyla grandella (Zeller) to Swietenia macrophylla Essential Oils - Marisi G. Soares; Luciane G. Batista-Pereira; João B. Fernandes; Arlene G. Corrêa; M. Fátima G. F. Da Silva; Paulo C. Vieira; Edson Rodrigues Filho; Orlando S. Ohashi (Journal of Chemical Ecology, 2003)